Acute Seizures Occurring in Association With SARS-CoV-2 - Hwang, Sean T.; Ballout, Ahmad A.; Mirza, Usman; Sonti, Anup N.; Husain, Arif; Kirsch, Claudia; Kuzniecky, Ruben; Najjar, Souhel (Frontiers in Neurology, 2020)
Seizures are an infrequent and serious neurological complication of SARS-CoV-2 infection with limited data describing the etiology and clinical context in which these occur, or the associated electrographic and imaging findings. This series details four cases of seizures occurring in patients with COVID-19 with distinct time points, underlying pathology, and proposed physiological mechanisms. An enhanced understanding of seizure manifestations in COVID-19 and their clinical course may allow for earlier detection and improved patient management.